ECONOMIC ASSESSMENT OF THE IMPLEMENTATION OF REGULATION OF THE MINISTER OF MARINE AND FISHERIES NUMBER 2 2015 - Darmawan Soecahyo (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Indonesia has an area of ocean that reaches 70% of the area of Indonesia. Judging from the results of such potential and should therefore be able to provide a very decent livelihood for fishing communities. Many marine areas in Indonesia are experiencing overfishing. Over exploitation of this fish occurs mostly in coastal areas. The purpose of this study was to determine the readiness of the fishing community in the implementation of the Regulation menyingkapi Minister of Marine and Fisheries No. 2 of 2015, and economic influence enactment of the Regulation Minister of Marine and Fisheries No. 2 in 2015. Methods of data collection is done by several techniques making that method interview, FGD as well as data documentation and literature, analysis using expert judgment. Fishermen feel unprepared due ver the gear used are derived from their ancestors and that's all they know. The use of trawl gear types and cantrang did have a good economic impact for fishermen but it would be bad for the environment while gill net fishing gear types have less positive impact on fishermen's income but will not have negative consequences for the environment in the preservation of biological resources. Viewed from the longest life cycle of the fish so if regulations Fisheries Minister is applied takes at least 7 to 9 years to return to normal with the efforts of all pihak.Rekomendasinya is the government provides continuous mentoring program on the use of new fishing gear, giving compensation to fishermen in the form of income support programs to the preservation of biological returned to normal and improve the environment continuously. Keyword : Readiness of fishing communities, economic studies fishermen, Regulation of the Minister of Marine and Fisheries No. 2 2015